2011
DOI: 10.1111/j.1528-1167.2011.03102.x
|View full text |Cite
|
Sign up to set email alerts
|

First‐ever, door‐to‐door cross‐sectional representative study in Prey Veng province (Cambodia)

Abstract: SUMMARYPurpose: To estimate the lifetime prevalence of epilepsy in Prey Veng province (Cambodia). Methods: Door-to-door screening was performed using a random cluster survey whereby all people >1 year of age were screened for epilepsy by using a validated and standardized questionnaire for epilepsy in tropical countries. Suspected epilepsy patients identified by the questionnaire were revisited and examined by epileptologists. The confirmation of epilepsy was based on an in-depth clinical examination. Electroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 17 publications
1
27
3
1
Order By: Relevance
“…Generalized seizures were the predominant pattern (68.7%) followed by partial seizures (29.8%). This was in contrast to some previous reports [10] but in agreement with others [3,4,5,9]. Conditions associated with symptomatic epilepsy were different between studies and included all major conditions.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Generalized seizures were the predominant pattern (68.7%) followed by partial seizures (29.8%). This was in contrast to some previous reports [10] but in agreement with others [3,4,5,9]. Conditions associated with symptomatic epilepsy were different between studies and included all major conditions.…”
Section: Discussioncontrasting
confidence: 56%
“…The average prevalence of epilepsy is estimated at 8 per 1,000 in the world population [1]. However, studies carried out in developing countries have reported higher rates [2] although many countries in Asia have reported lower rates compared to sub-Saharan or Latin American countries [3]. In Algeria, as in the other countries of North Africa, epilepsy remains an important public health issue with medical, economic and sociocultural implications.…”
Section: Introductionmentioning
confidence: 99%
“…In many LMICs this approach makes possible the estimation of the burden of epilepsy more rapidly in a given setting at a much lower cost. Most frequently, villages are taken as clusters [21]. They are selected by lot to have all their inhabitants included in the survey.…”
Section: Methodsmentioning
confidence: 99%
“…For the first time, the France-based INSERM Institute of Tropical Neurology (IENT) along with its collaborators investigated epilepsy in Cambodia and estimated in a representative manner that Cambodia has about 86,000 (mean) people with epilepsy [9]. This provides the Cambodian government (and its financiers) with a representative figure on which to base their policies and mobilize their funds.…”
Section: Cambodiamentioning
confidence: 99%
“…Many of these cases were never offered a diagnosis or treatment [11], and thus our work has at least helped to bring them ‘out of the epilepsy shadow’. These surveys yielded a lifetime prevalence of 5.8/1,000 (lower than in SSA), a predominance of generalized seizures, a young mean age of the cases, and a male predominance [9], somewhat similarly to what has been observed in other REP countries [4,5]. Subsequent surveys [11] have shown several particularities, for instance the predominant importance of pregnancy- and birth-related risk factors, absence of a supernatural belief or absence of specific contagions such as blood, low use of traditional therapies, absence of use of spiritual intervention as treatment, etc.…”
Section: Cambodiamentioning
confidence: 99%